Linux troubleshooting course with real life examples - Afzal, Imran (Packt Publishing, 2019)
"Explore the key tips and techniques for maintaining a reliable and highly available Linux server infrastructure and reducing downtime with this interactive course. Beginning with troubleshooting best practices, you'll go on to understand the technique of effectively diagnosing and fixing common and complex Linux server configuration and administration issues. From system access troubleshooting through to filesystem troubleshooting, you'll learn with practical examples and tackle a variety of critical issues. Later, you'll even get to grips with system recovery. All along, this course will guide you on how to apply your skills in a production environment. By the end of this course, you will have developed the skills you need to effectively troubleshoot a variety of Linux-related issues."--Resource description page